2012
DOI: 10.1627/jpi.55.308
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Isobutane by 1-Butene over H-beta Zeolite in CSTR (Part 2) Deactivation Mechanism of Zeolite Catalyst and Optimization of CSTR Conditions

Abstract: DGC-H-beta zeolite catalyst has higher activity and selectivity for the alkylation of isobutane with 1-butene in a CSTR. The cause of the deactivation of the catalyst and the optimum reaction conditions were investigated. Deactivation of the catalyst was caused not by adsorbed carbon species but by hydrocarbons formed by multiple alkylation or oligomerization of olefin. Optimized conditions to avoid these reactions achieved stable selective alkylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…2,3,3,-TMP and dimethylhexane were formed in only small amounts. As previously reported 11), 12) , these selectivities for C8 alkylate were typical for alkylation using H-BEA zeolites.…”
Section: Catalytic Experimentssupporting
confidence: 88%
See 1 more Smart Citation
“…2,3,3,-TMP and dimethylhexane were formed in only small amounts. As previously reported 11), 12) , these selectivities for C8 alkylate were typical for alkylation using H-BEA zeolites.…”
Section: Catalytic Experimentssupporting
confidence: 88%
“…The catalytic reaction was performed in a CSTR (continuous stirred tank reactor) with 30 mL volume 11), 12) . Reaction conditions were as follows; temperature 363 K, pressure 2.0 MPa, and stirring rate 780 rpm.…”
Section: Catalytic Experimentsmentioning
confidence: 99%
“…Deactivation may also occur due to the effect of hydrocarbons formed by multiple alkylations or oligomerizations of olefin. Sekine’s group studied the deactivation mechanism of zeolite catalyst in a continuously stirred tank reactor (CSTR); the zeolite was prepared via the sol–gel drying method with SiO 2 /Al 2 O 3 = 30. The results demonstrated that lower olefin space velocity and higher amount of zeolite enabled stable activity for the alkylation over the synthesized zeolite, which could promote hydride transfer from isobutane to C 8 cation (single alkylation) and suppress multiple alkylations and olefin oligomerization .…”
Section: Recent Progress On Solid Acid Catalysts For Alkylationmentioning
confidence: 99%
“…Sekine’s group studied the deactivation mechanism of zeolite catalyst in a continuously stirred tank reactor (CSTR); the zeolite was prepared via the sol–gel drying method with SiO 2 /Al 2 O 3 = 30. The results demonstrated that lower olefin space velocity and higher amount of zeolite enabled stable activity for the alkylation over the synthesized zeolite, which could promote hydride transfer from isobutane to C 8 cation (single alkylation) and suppress multiple alkylations and olefin oligomerization . Fortunately, the deactivation of zeolites was reversible and could be entirely recovered by several treatments; for example, coked zeolite is regenerated by both partial liquid-phase hydrogenative treatment at reaction conditions and complete liquid-phase hydrogenative regeneration at high temperature, as hydrogen was shown to be very effective for the regeneration of the catalysts. , Y zeolites are the most studied catalysts for alkylation, as they proved to be less prone to deactivation than other types of zeolites such as zeolite X, mordenite, ZSM, and MCM-1 and showed high selectivity to isooctane.…”
Section: Recent Progress On Solid Acid Catalysts For Alkylationmentioning
confidence: 99%